2019
DOI: 10.1093/asj/sjz253
|View full text |Cite
|
Sign up to set email alerts
|

Social Media’s Influence on Breast Augmentation

Abstract: Background The purpose of this study is to evaluate if and what social media use influences our patients’ decisions to undergo breast augmentation. Objectives A single-institution study was designed to evaluate women who underwent elective breast augmentation from 2017 to 2018. Methods Patients were contacted via validated, prompted telephone survey. Data reg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 15 publications
0
7
0
Order By: Relevance
“…Instagram was found in a majority of studies to generate the highest engagement, especially among younger audiences. 8 , 19 , 27 , 28 , 30 , 33–36 YouTube and TikTok were found to have high engagement, but overall low-quality content. 28 , 29 , 31 , 32 One study that utilized crowd-sourcing found Facebook to be the optimal platform for engagement.…”
Section: Resultsmentioning
confidence: 92%
See 1 more Smart Citation
“…Instagram was found in a majority of studies to generate the highest engagement, especially among younger audiences. 8 , 19 , 27 , 28 , 30 , 33–36 YouTube and TikTok were found to have high engagement, but overall low-quality content. 28 , 29 , 31 , 32 One study that utilized crowd-sourcing found Facebook to be the optimal platform for engagement.…”
Section: Resultsmentioning
confidence: 92%
“… 30 Instagram is the most powerful tool that influences patients’ desire to undergo breast augmentation. 33 Alghonaim et al found that 81% of patients that visited a facial plastics clinic were between the ages 25 and 34. 97% found that cosmetic social media accounts were helpful.…”
Section: Resultsmentioning
confidence: 99%
“…In this context, the EVERA device may not be an excessively demanding procedure. This advantage can be further highlighted in our social networking era and for generation Z [17,18].…”
Section: Discussionmentioning
confidence: 95%
“…This finding could be attributable to the broad prevalence of cosmetic breast surgeryrelated content on social media. 16 When considering the causes for these differences in patient distribution, the quality and quantity of information posted is important to consider. For example, surgery-specific materials that patients received or were posted on these social media sites could have been either harder or easier to understand depending on the target audience.…”
Section: Discussionmentioning
confidence: 99%